Nondermal irritating hyperosmotic nanoemulsions reduce treatment times in a contamination model of wound healing. Issue 4 (3rd June 2016) - Connell, Sean; Li, Jianming; Durkes, Abigail; Zaroura, Mohammed; Shi, Riyi
Abstract: Increased microbial burden within the wound often complicates wound healing and may lead to subsequent infection or delayed healing. Here, we investigate a novel topical for addressing wound contamination that utilizes hyperosmotic saccharides with a cell membrane disrupting emulsion. These hyperosmotic nanoemulsions (HNE) were administered topically in a full‐thickness biopsy model of wound healing. Results show that HNE were well tolerated in noninfected animals with no indications of dermal irritation or acute toxicity. Additionally, HNE was able to reduce bacterial bioburden ( Escherichia coli and Enterococcus faecalis ) levels by 3 logs within 24 h when wounds were inoculated with 5 × 10 6 total CFU. These bactericidal values were similar to wounds treated with silver sulfadiazine. Wound closure showed HNE wounds closed in 7.6 ± 0.2 days while SSD and control required 10.2 ± 0.4 and 10.4 ± 0.3 days, respectively. HNE maintained a moist wound environment, were well debrided, and exhibited improved hemostatic response. Further histological examination revealed enhanced granulation tissue as compared to silver sulfadiazine and control cohorts. These results were corroborated with 3D topographical imprints of the wounds at day 14 which qualitatively showed a smoother surface. In contrast, silver sulfadiazine appeared to delay wound closure. Finally, dermal sensitization and irritation studies conducted in guinea pig and rabbits did not reveal any acute dermal side effects from HNE exposure. The cumulative data indicates nonantibiotic‐based HNEs may be a promising topical treatment for the management of contaminated wounds.